A case report of neuromyelitis optica spectrum disorder with peripheral neuropathy as the first episode. Issue 10 (March 2018) - Chi, Lu-Mei; Gao, Yu; Nan, Guang-Xian
Abstract: Rationale: Neuromyelitis optica spectrum disorders (NMOSDs) represent recurrent autoimmune diseases, generally beginning with optic nerve neuritis or acute transverse myelitis. Patient concerns: A 57-year-old male with long-term alcohol intake was hospitalized because of limb numbness. EMG examination showed the peripheral sensory nerve was in demyelination and an axonal injury was found. His symptoms could not be improved by vitamin B injection but were later significantly attenuated by dexamethasone treatment. Four months later, symptoms of optic neuritis in the left eye appeared, and 6 months later he exhibited peripheral neuropathy with acute myelitis. Diagnoses: He was diagnosed NMOSD. Outcomes: Immunotherapy improved his peripheral neuropathy and myelitis symptoms. Lessons: NMOSD patients could represent peripheral neuropathy as the first episode.